Tax Planning in Personal Income Tax: A Systematic Literature Review - Abdurrauf Umar; Ida Farida Adi Prawira; Memen Kustiawan (Jurnal Pendidikan Akuntansi (JPAK), 2023)
The systematic literature review analyses and synthesizes research conducted regarding personal income tax planning within the time period of 2012 to 2022, 30 articles were reviewed. The review discovered that most of the articles dwelled mostly on unincorporated businesses and their owners/entrepreneurs/sole proprietors/investors as well as those articles that discussed issues relating to tax authorities’ regulations on personal income tax. The articles reviewed, gave insights on issues relating to personal income tax planning of wealth transfers, such as inheritance and bequest; gifts and inta-vivos; deathbed planning, etc. Importantly, they provided insights into how unincorporated businesses and entrepreneurs can optimize their disposable income through good personal income tax planning. In addition to the above, it highlighted such financial instruments that were resorted to, the most by taxpayers, which made their personal income tax planning more effective. (life insurance policies are the most widely used tax-saving tool, followed by provident funds and tax-saving fixed deposits, loans for homes and schools, National Savings Certificates, unit-linked insurance plans, health insurance plans, and equity-linked savings schemes, Infrastructure Bonds, in that order); we also found out that government strategies that influenced tax planning in favour of the state include: cooperation, increased uncertainty, creation of models, and maintaining a friendly atmosphere to avoid aggressive tax planning and improve revenue. Finally, direction for future research was suggested.